The policy of transfer of curricular reforms between Spain and Brazil. Towards the psychologization of education (Revista Lusófona de Educação, 2023)
In order to adapt the organization and functioning of the educational system to the constitutional requirements derived from the document of 1978, the Spanish educational reform of the 1980s and 90s went beyond the national borders encompassing international spaces. In its broad and firm expansion to different countries of the Latin American orbit, we want to show how it had a special impact on the reform of the Brazilian education agreed in the nineties reflecting on its development, especially, in the PCNs (National Curricular Parameters). We approach this analysis, derived from the application of the Systematic Literature Review method, which we anticipate of high value and interest, from a threefold dimension that seeks to investigate the influences of Spanish educational policies on Brazil. Firstly, we make use of the essential and classic contribution on school culture made by Professor Escolano (2000). Secondly, we advance until we approach curriculum design (what we understand as“the discourse”) and its consequent projection. And finally, thirdly, we analyze the tensions between psychologists and pedagogues both in interpretative and academic terms that were illustrated in conferences, congresses, seminars and, of course, in the publication of books, articles and reports.Key words: educational system; psychological and pedagogical reform; influences of educational policies; Spain; Brazil.